2021
DOI: 10.1108/ecam-04-2020-0235
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interactive virtual reality for furniture, fixture and equipment design communication: an empirical study

Abstract: PurposeThis study aims to propose a novel approach to developing an interactive and immersive virtual environment for design communication in the furniture, fixture and equipment (FFE) sector. The study further investigates its effectiveness in enhancing the design communication and coordination between the stakeholder.Design/methodology/approachQuasi-experimental research was adopted involving 12 FFE professionals, designers and end-users in single-group pre-test-post-test design. The tests were performed pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Yet, a key limitation lies with this focus is that studies have tended to narrowly analyse particular technologies in isolation. So, in Prabhakaran's et al (2021) case, the focus is on virtual reality, and in Adinyira et al (2021), the focus is on machine learning. This therefore raises the question of how we evaluate what happens when a constellation of technologies is at play?…”
Section: Materials Agency: Ask Not What Humans Can Do To Make Industry 40 Work…mentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, a key limitation lies with this focus is that studies have tended to narrowly analyse particular technologies in isolation. So, in Prabhakaran's et al (2021) case, the focus is on virtual reality, and in Adinyira et al (2021), the focus is on machine learning. This therefore raises the question of how we evaluate what happens when a constellation of technologies is at play?…”
Section: Materials Agency: Ask Not What Humans Can Do To Make Industry 40 Work…mentioning
confidence: 99%
“…These papers share a common thread that Industry 4.0 technologies have the potential to bring different stakeholders together to co-produce the future. In the fifth paper of this special issue, for instance, Prabhakaran et al (2021) combined BIM and virtual reality in a quasi-experiment involving 12 professionals, designers and endusers in furniture, fixture and equipment design. They found that significantly less time was needed for decision-making, due to the virtual reality platform offering a synchronised collaborative opportunity for designers and end-users to test and review options.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This potential of VR has attracted the attention of researchers from various sectors of the Architecture Engineering and Construction (AEC) industry, including the Furniture, Fixture and Equipment (FFE) sector. The FFE sector often communicates its designs with its stakeholders using traditional methods such as two-dimensional drawings/sketches (2D) and brochures (Prabhakaran et al, 2021). It has been noted in previous studies that the design decisions of stakeholders are strongly affected by the aesthetics of the FFE element and how well it blends with the architectural aspects of the building (Pakarinen & Asikainen, 2001;Prabhakaran et al, 2021).…”
Section: Introductionmentioning
confidence: 99%